O FUNGO Aspergillus SP. COMO PROVÃVEL AGENTE DE CONTROLE BIOLÃ“GICO DE Spadoptera frugipera (J. E. SMITH, 1797) - Watanabe, M. A.; Fuini, L. C. (REVISTA DE AGRICULTURA, 2015)
O FUNGO Aspergillus SP. COMO PROVÃVEL AGENTE DE CONTROLE BIOLÃ“GICO DE Spadoptera frugipera (J. E. SMITH, 1797)